Development of Cognitive Competences of Future Teachers on the Basis of Interdisciplinary Relationship - Aibakhar Nurmukhanbetovna Jumamuratova (Genius Journals, 2023)
The requirements of State educational standards developed in the disciplines at all stages of education provide not only deep knowledge and education for young people, but also the tasks of preparing young people who are the creators of tomorrow for the next stages of Education. This necessitates the effective use and improvement of training and educational work in its place of mechanisms of interaction with each other in educational disciplines of significant didactic importance at all stages of the current educational system. The process of integration of subjects at all stages of Education shows that the targeted use of the features of their interaction in the teaching of subjects, the pedagogical and methodological correct Organization of classes, guarantees the meaningful and high-quality teaching of each subject
Keywords: interdisciplinary; integration; general professional competences